All-Range Black Spruce Picea-Mariana Provenance Study in Newfoundland: Performance and Genotypic Stability of Provenances - Khalil, M.A.K. (JD Sauerlaender's Verlag, 1984)
The paper presents ten year results of a three-location all range black spruce provenance study in Newfoundland, conducted in six-replicated triple lattice design experiments. The data, collected in 1980 on 1979 and 1980 heights, 1980 diameter at 0.3 m, height growth in the 1974-80 period and in 1980 were analysed with analyses of variance by and over locations, BoNFERRONI t-tests, step-wise regression analyses and evaluation of the provenances for productive quality and genotypic stability, using height growth in the 1974-80 period as the criterion. Lattice design proved significantly effective in removing intra-replication variation and in improving efficiency compared with the randomized complete block design. High intra-provenance variation was noticed, indicating heterogeneity of the provenances and the possibility of obtaining enhanced genetic gains by intensive family selec tions within superior provenances. Most of the provenances in the fourth quartile belong to the region between latitudes.45°-49' 6 N and longitudes 60°-84° W. Variation in the performance of provenances among locations was detected in arrays and confirmed and quantified by analyses of variance over locations. Initial height growth in nursery, six-year growth in field and total growth are significantly correlated with each other. Superior provenances have relatively low genotypic stabi lity, which appears to be due to their high heterozygosity. Eight promising provenances have been tentatively iden tified by a combined evaluation of the productive quality and genotypic stability of all provenances. These are: MS. 1531, S.6905, MS. 1528, MS. 1533, S.6927, 370, S.6911 and 353.